PERANCANGAN SISTEM MONITORING ENERGI BERBASIS INTERNET OF THINGS PADA PEMBANGKIT LISTRIK TENAGA PIKOHIDRO - Jenko Antofa Gasta Ananda (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Abstract. Global awareness of carbon emission reduction and sustainable use of natural resources encourages the use of renewable energy, including PicoHydro Power Plants (PLTPH). This study aims to develop an Internet of Things (IoT) based energy monitoring system at PicoHydro Power Plants (PLTPH). Internet of Things (IoT) is used to collect real-time data on operational conditions, including Voltage, current, power, frequency, and power factor. AC Voltage from the generator is connected to the input of PZEM-017 and PZEM-004T. The ESP8266 Wi-Fi module sends data to the picohidro. elektroloss.id Web Server. Testing of the PZEM-017 sensor shows an average error of 0.52% for Voltage and 0.69% for current, while the PZEM-004T shows an average error of 0.39% for Voltage and 0.61% for current. Based on the test results of the PZEM-017 and PZEM-004T sensors, it can be concluded that the sensors are working well, with error values ​​below 1%. The website displays the sensor measurement results remotely in real time.